PENGARUH TERAPI KOMBINASI PROGRESSIVE MUSCLE RELAXATION DAN AROMATERAPI LEMON TERHADAP NYERI PADA PASIEN KANKER - Erna Melastuti; Rika Viyanti; Suyanto Suyanto (Jurnal Keperawatan dan Kesehatan, 2021)
Background: Cancer pain is caused by the growth of cancer mass that is getting bigger so that it suppresses bones, tissues and other organs around it. Cancer pain is a common complaint of post-treatment patients. Pain that is not further identified will have an impact on the patient's activity. Pain management can be done by pharmacological and nonpharmacological measures. Nonpharmacological therapies include progressive muscle relaxation and lemon aromatherapy. Aim : This study aimed to determine the effect of progressive muscle relaxation and lemon aromatherapy of cancer’s patient. Method : Pre Experiment used One Group With Pretest — Posttest Design. The sample consisted of 9 respondents using nonprobability sampling technique with purposive sampling method. Result : The results of this research is Wilcoxon Signed Rank Test with a maximum level of 95%, obtained p value of 0.006 less than the significant value of 0.05. Conclusion : There is an effect of progressive muscle relaxation and aromatherapy lemon on pain in cancer patients with a p value of 0.006. Keywords : Progressive muscle relaxation, lemon aromatherapy, pain, cancer